Survival fluctuation is linked to precipitation variation during staging in a migratory shorebird - Brlík, Vojtěch; Pakanen, Veli-Matti; Jaakkonen, Tuomo; Arppe, Heikki; Jokinen, Jaakko; Lakka, Johanna; Blomqvist, Donald; Hahn, Steffen; Valkama, Jari; Koivula, Kari (Scientific reports, 2022)
Understanding how weather conditions affect animal populations is essential to foresee population changes in times of global climate shifts. However, assessing year-round weather impacts on demographic parameters is hampered in migratory animals due to often unknown occurrence in space and time. We addressed this by coupling tracking and weather data to explain extensive variation in apparent survival across 19 years in a northern European population of little ringed plovers (Charadrius dubius). Over 90% (n = 21) of tracked individuals followed migration routes along the Indo-European flyway to south India. Building on capture-recapture histories of nearly 1400 individuals, we found that between-year variation in precipitation during post-breeding staging in northern South Asia explained 47% of variation in apparent adult survival. Overall, the intensity of the monsoon in South Asia explained 31-33% of variability in apparent survival. In contrast, weather conditions in breeding, final non-breeding and pre-breeding quarters appeared less important in this species. The integration of multi-source data seems essential for identifying key regions and periods limiting population growth, for forecasting future changes and targeting conservation efforts.
Keywords: klimatické změny; podnebí; počasí; roční období; Animals; Charadriiformes; Climate Change; zvířata; Climate; Weather; Seasons